Green Growth, Green Technology, and Environmental Health: Evidence From High-GDP Countries - Hussain, Zahid; Mehmood, Bilal; Khan, Muhammad Kaleem; Tsimisaraka, Raymondo Sandra Marcelline (Frontiers in Public Health, 2022)
Green growth is an exceptional strategy for sustainable development. It provides the pathways to combat the environmental issues and the use of natural resource. This study investigates the effects of green technology and environmental factors on green growth in high-GDP countries from 2000 to 2020. In addition, it also probes the linear and non-linear effect of gross domestic product on green growth. To do so, we employ advanced econometric approach e.g., cross-sectional autoregressive distributed lags estimator for long and short runs. The outcomes demonstrate that linear effect of GDP is positive for green growth. On the contrary, non-linear effect of GDP has negative magnitude for green growth. Besides, green technology substantially increases the green growth. The energy consumption is found to be important influencer, and it decreases the green growth. Findings further suggest that environmental factors such as emissions reduce the green growth in the sample countries. It is worth note that joint effect of energy consumption and emissions deteriorate the green growth in the countries. Based on empirical findings, for policy makers, this study suggests that high-GDP countries should manage their economic and environmental activities in order to increase the green growth that may protect the ecological environment.